Rural Development As Strategy for Food Security and Global Peace in The 21st Century - Nwagboso, I. Christopher (Mediterranean Journal of Social Sciences, 2012)
This paper discusses rural development as strategy for food security and global peace in the century. The paperadopts descriptive methodological orientation to investigate how the abysmal failure of governments in the contemporary worldto develop their rural areas has adversely impacted on food security. However, the paper argues that why the quest for ruraldevelopment has remained elusive particularly in the developing countries is largely due to up-bottom approach currentlyadopted by countries. It further argues that this strategy has not only resulted to abject poverty in most countries, but also failedto achieve food security among individuals, families and communities around the globe. The implication of this sorry state ofaffairs is that the attainment of global peace in the 21st century has remained an exercise in futility in spite of the overdramatizedefforts of international organizations like the UN. The paper, therefore, recommends among others, the need toestablish a specialized agency to study the success of rural development policies and programmes in some countries like Chinaand replicate such strategies in other parts of the world for effective food security on global peace in the 21st century.